2023
DOI: 10.1039/d3qi00297g
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-linear CuX2(X = Cl, Br) motif-built hybrid copper halides realizing encouraging nonlinear optical activities

Abstract: The emerging organic−inorganic hybrid metal halides feature unique optical and electronic properties, easily grown up, and flexible crystal structures, making them to be a class of promising next-generation nonlinear optical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…11,12 In addition, the 0D metal halides are composed of different metal ions and halogen ligands with diverse coordination modes, such as the trigonal plane, tetrahedron, octahedron, and square pyramid, and thus endow them with rich physical properties, including tunable emission, nonlinear optical, and ferroelectric behaviors. 13–15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In addition, the 0D metal halides are composed of different metal ions and halogen ligands with diverse coordination modes, such as the trigonal plane, tetrahedron, octahedron, and square pyramid, and thus endow them with rich physical properties, including tunable emission, nonlinear optical, and ferroelectric behaviors. 13–15…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we adjusted the copper–bromine inorganic unit by reasonably controlling the feed ratio of (EtPh 3 P) and CuBr and synthesized three copper bromides (EtPh 3 P)CuBr 2 ( 112 ), (EtPh 3 P) 2 Cu 2 Br 4 ( 224 ), and (EtPh 3 P) 2 Cu 4 Br 6 ( 246 ). In particular, they crystallize with different crystal structures; that is, 112 adopts a noncentrosymmetric (NCS) space group ( P 2 1 ) with a quasi-linear [CuBr 2 ] − framework, which has been reported very recently, exhibiting encouraging nonlinear optical activity, 13 while 224 and 246 are crystalized in a centrosymmetric (CS) space group ( P 2 1 / c for 224 and P 2 1 / n for 246 ) with [Cu 2 Br 4 ] 2− dimers and [Cu 4 Br 6 ] 2− clusters, respectively. We systematically compared the structures and optical properties of three types of Cu–X units, excluding the interference of organic cations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, π-conjugated planar organic moieties have been successfully developed as potential NLO-active groups due to their large polarizability anisotropy, ultrafast response time, and infinite design probabilities. When the organic moieties act as anions, for instance, the (H x C 3 N 3 Q 3 ) (3– x )– (Q = O, S; x = 0, 1, and 2) groups have been harnessed to build many SHG crystals such as Ca 3 (C 3 N 3 O 3 ) 2 (SHG: >2 × β-BaB 2 O 4 ), KLi­(HC 3 N 3 O 3 )·2H 2 O (5.3 × KDP), RE 5 (C 3 N 3 O 3 ) (OH) 12 (RE = Y, Yb, and Lu) (2.5–4.2 × KDP), and Cs 3 Cl­(HC 3 N 3 S 3 ) (11.4 × KDP). Theoretical calculations revealed that the organic moieties dominate the SHG effects of these materials. The organic groups can also function as cations, for example, the [C­(NH 2 ) 3 ] + group has been widely used as a SHG building group as in [C­(NH 2 ) 3 ] 6 (PO 4 ) 2 ·3H 2 O (3.8 × KDP), C­(NH 2 ) 3 SO 3 F (5 × KDP), and [C­(NH 2 ) 3 ] 2 [B 3 O 3 F 4 (OH)] (1.4 × KDP). , It is noticed that the pyridine and pyrimidine derivative groups featuring nitrogen-containing heteroaromatic rings could be protonated and used to build organic–inorganic hybrid SHG crystals such as [ o -C 5 H 4 NHOH] 2 [I 7 O 18 (OH)]·3H 2 O (8.5 × KDP), (C 5 H 6 ON) + (H 2 PO 4 ) − (3 × KDP), and (C 4 H 6 N 3 ) + (H 2 PO 3 ) − (2 × KDP). ,, …”
Section: Introductionmentioning
confidence: 99%
“…When the alkali metal ions of inorganic metal halides are replaced by organo-ammonium cations, many HMHs formed possess noncentrosymmetric structures as well and generate a second-order NLO effect. In addition, some of them exhibit considerable second harmonic generation (SHG) strength, such as [CH 3 NH 3 ]­GeI 3 , NH­(CH 3 ) 3 SnCl 3 , NH­(CH 3 ) 3 SnBr 3 , [NH 2 (CH 2 CH 3 ) 2 ] 3 BiBr 6 , Gua 3 Cu 2 I 5 , (C 20 H 20 P)­CuX 2 (X = Cl, Br), etc. Nonetheless, those SHG-active HMHs represent only a small fraction of all HMHs that have been excavated so far .…”
Section: Introductionmentioning
confidence: 99%